Utility of remote monitoring in patients on automated peritoneal dialysis - Ramón Paniagua; Marcela Ávila-Díaz; Miguel Á. Trejo-Villeda; Alma S. Bernal-Amador; Alfonso Ramos (Permanyer, 2023)
Home hemodialysis (HD) and automated peritoneal dialysis (APD) have advantages over HD in hospitals or HD centers. Home therapies are generally less expensive and give patients greater mobility and freedom for work, school, family, and recreational activities. Technological advances have made it possible to complement APD with devices for remote monitoring (RM) of the patient. With them, objective information generated in the APD device is collected and sent to repositories "in the cloud" for analysis or at the time decided by the health team. With APD+RM, it is possible to monitor therapeutic compliance, effective dialysis time, ultrafiltration volumes, inflow and outflow patterns of dialysis fluid, and patient actions to respond to alarms that indicate deviations from the parameters set by the nephrologist. The results of APD+RM show good acceptance by the patient, nephrologists, and nurses, treatment adherence has improved, hospitalizations and technique failure have decreased, and some aspects of quality of life have improved. However, there is a lack of controlled clinical trials that reliably demonstrate lower mortality and comorbidity due to specific causes.